Pengaruh Penerapan Good Corporate Gorvanance, Sistem Pengendalian Internal dan Kompetensi Terhadap Kinerja Lembaga Perkreditan Desa (LPD) Se-Kota Denpasar - Ni Kadek Desi Dwi Lestari; Rai Dwi Andayani (Hita Akuntansi dan Keuangan, 2023)
This study is motivated by the problems faced by the Village Credit Institutions when operating with the aim of improving the good performance of the LPD, although the LPD still faces many obstacles that make it difficult to achieve this goal. This goal becomes difficult. performance of LPD. The aim of this study was to determine the impact of good corporate governance practices, internal control systems and skills on the performance of village credit institutions across Denpasar city. The non-probability sampling method was combined with the Saturated sampling technique, namely all LPD employees in Denpasar City with a total of 85 people using the Slovin Formula.The analytical technique used is multivariable linear regression analysis to conclude that good corporate governance practices, internal control systems and skills have a positive and significant impact on operational performance. Activities of village credit institutions throughout the city of Denpasar. It is recommended that the City of Denpasar LPD conduct socializing with village residents on LPD governance, regular management meetings regarding financial reporting, and each staff member being assigned special training village community services to improve LPD performance across Denpasar city.